RETRACTED: miR-335 Targets LRRK2 and Mitigates Inflammation in Parkinson’s Disease - Oliveira, Sara R.; Dionísio, Pedro A.; Gaspar, Maria M.; Correia Guedes, Leonor; Coelho, Miguel; Rosa, Mário M.; Ferreira, Joaquim J.; Amaral, Joana D.; Rodrigues, Cecília M. P. (Frontiers in Cell and Developmental Biology, 2021)
Parkinson’s disease (PD) is mainly driven by dopaminergic neuronal degeneration in the substantia nigra pars compacta accompanied by chronic neuroinflammation. Despite being mainly sporadic, approximately 10% of all cases are defined as heritable forms of PD, in which mutations in the leucine-rich repeat kinase (LRRK2) gene are the most frequent known cause of familial PD. MicroRNAs (miRNAs or miRs) including miR-335 are frequently deregulated in neurodegenerative diseases, such as PD. Here, we aimed to dissect the role of miR-335 in protecting from inflammatory and/or neurodegenerative events in experimental models of PD. Our results showed that miR-335 is significantly downregulated in different PD-mimicking conditions, including BV2 microglia cells stimulated with lipopolysaccharide (LPS) and/or overexpressing wild-type LRRK2. Importantly, these results were confirmed in serum of MPTP-injected mice and further validated in patients with idiopathic PD (iPD) and those harboring mutations in LRRK2 (LRRK2-PD), corroborating potential clinical relevance. Mechanistically, miR-335 directly targeted LRRK2 mRNA. In the BV2 and N9 microglia cell lines, miR-335 strongly counteracted LPS-induced proinflammatory gene expression, and downregulated receptor interacting protein 1 (RIP1) and RIP3, two important players of necroptotic and inflammatory signaling pathways. Further, miR-335 inhibited LPS-mediated activation of ERK1/2 cascade. LRRK2-Wt-induced proinflammatory gene expression was also significantly reduced by miR-335 overexpression. Finally, in SH-SY5Y neuroblastoma cells, miR-335 decreased the expression of pro-inflammatory genes triggered by α-synuclein. In conclusion, we revealed novel roles for miR-335 in both microglia and neuronal cells that strongly halt the effects of classical inflammatory stimuli or LRRK2-Wt overexpression, thus attenuating chronic neuroinflammation.